Biosorption of Hexavalent Chromium Using Bacillus Licheniformis Isolated From Effluent Sample - Ajmal ahamed, A (International Journal of Pharmaceutical & Biological Archive, 2014)
Biosorption of Hexavalent Chromium Using Bacillus Licheniformis Isolated From Effluent Sample